Penerapan Model Pembelajaran Student Facilitator and Explaining untuk Meningkatkan Hasil Belajar Bahasa Indonesia Peserta Didik Kelas IV A SD Aisyiyah Muhammadiyah Makassar - Nurannisa Azzahrah; M. Agus; Besse Syukroni (Jurnal Pendidikan dan Sastra Inggris, 2025)
The purpose of this study was to improve students' learning outcomes in the Indonesian language subject through the application of the Student Facilitator and Explaining model on the One Point material. The factors underlying this study were learning problems experienced by students such as low Indonesian language learning outcomes below the KKTP standard. The research approach used was classroom action research conducted in 2 cycles where each cycle was carried out in 2 meetings. The results of the study showed that there was an increase in student learning outcomes as seen from the tests obtained from cycle I and cycle II. The results of the cycle I evaluation test with a percentage of learning outcomes of 50% and increased in cycle II with a percentage of learning outcomes of 88%. Based on the results of the evaluation of cycles I and II and the reflections that have been carried out, it can be concluded that by implementing the student facilitator and explaining learning model in the Indonesian language subject of class IV A SD Aisyiyah Muhammadiyah 3 Makassar, it can improve student learning outcomes.